MALT1 – a universal soldier: multiple strategies to ensure NF‐κB activation and target gene expression. (10th June 2015) - Afonina, Inna S.; Elton, Lynn; Carpentier, Isabelle; Beyaert, Rudi
<x xml:space="preserve">Abstract</x> The paracaspase MALT1 (mucosa associated lymphoid tissue lymphoma translocation gene 1) is an intracellular signaling protein that plays a key role in innate and adaptive immunity. It is essential for nuclear factor κB (NF‐κB) activation and proinflammatory gene expression downstream of several cell surface receptors. MALT1 has been most studied in the context of T‐cell receptor‐induced NF‐κB signaling, supporting T‐cell activation and proliferation. In addition, MALT1 hyperactivation is associated with specific subtypes of B‐cell lymphoma, where it controls tumor cell proliferation and survival. For a long time, MALT1 was believed to function solely as a scaffold protein, providing a platform for the assembly of other NF‐κB signaling proteins. However, this view changed dramatically when MALT1 was found to have proteolytic activity that further fine‐tunes signaling. MALT1 proteolytic activity is essential for T‐cell activation and lymphomagenesis, suggesting that MALT1 is a promising therapeutic target for the treatment of autoimmune diseases and distinct lymphoma entities. However, interference with MALT1 activity may pose a dangerous threat to the normal functioning of the immune system and should be evaluated with great care. Here we discuss the current knowledge on the scaffold and protease functions of MALT1, including an overview of its substrates and the functional implications of their cleavage.